Implementasi P5 Pada Tema Gaya Hidup Berkelanjutan Dalam Mengembangkan Kreativitas Peserta Didik Kelas IV di SDN Sukasari 4 - Khumairoh, Ifdathi Zahra; Pribadi, Reksa Adya; Syachruroji, Ahmad (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This study aims to describe the implementation of P5 on the theme of sustainable lifestyle in developing the creativity of fourth grade students at SDN Sukasari 4. This study was conducted in April 2025 at SDN Sukasari 4, Tangerang City. This study uses a descriptive qualitative approach with interview, observation and documentation data collection techniques. The results of the study indicate that the implementation of P5 on the theme of sustainable lifestyle shows a positive impact in developing the creativity of fourth grade students at SDN Sukasari 4. The activities designed contextually and collaboratively have succeeded in encouraging students to think more openly, imaginatively, and be able to find solutions in dealing with problems that occur in the surrounding environment. In addition, the creativity of fourth grade students at SDN Sukasari 4 also shows good development. Students are able to express original ideas in the form of works such as making ecoprint batik and group presentations that illustrate their understanding of issues in the surrounding environment. Through P5 activities, students are directly involved in collaborating, and expressing their ideas in creative, unique, and different ways. Overall, P5 activities provide opportunities for students to develop their creativity not only in the form of product creations, but also in their mindset, collaboration, and active involvement in contextual learning that is relevant to everyday life.